A multi-centre, randomized, non-inferiority trial to compare ulipristal with standard surgical treatment in women with symptomatic uterine fibroids: Protocol of the MYOMEX-2 trial. (January 2021) - Middelkoop, Mei-An; Huirne, Judith A.F.; van der Weide, Marijke C. Jansen; Bosmans, Judith E.; Hehenkamp, Wouter J.K.
Highlights: First RCT to compare long term intermittent treatment with ulipristal to surgery. Primary outcome: change in symptom severity. Secondary outcomes: e.g. quality of life, sexuality, fibroid volume, liver function. Cost-effectiveness will be compared. Abstract: Objectives: Fibroids are the most common benign tumours found in the uterus and can cause various symptoms. In 20–50 % of the women, an intervention is required. When conservative options fail, invasive options such as hysterectomy, uterine artery embolization or myomectomy are eligible options. Ulipristal acetate (UPA) was launched as the sole available long term pharmaceutical treatment, with the potential to avoid surgery. It is suggested that UPA improves quality of life, reduces symptoms and fibroid volumes. However, UPA is an expensive medicine, is possibly associated with liver injury and has never been directly compared to surgical treatment. The aim of this trial is to compare UPA to surgical treatment on both effectiveness and cost-effectiveness. Primary outcome is the reduction in symptom severity scores (part of the Uterine Fibroid Symptom and Quality of Life questionnaire) at 24 months of follow-up compared to baseline. Secondary outcomes include quality of life, societal costs, societal participation, liver function variation, patient satisfaction and preference. Outcomes will be analysed according to intention-to-treat principle. Study Design: The MYOMEX-2 trial is an open-label, multicentre, non-inferiority randomized controlled trial. Patients are pre-menopausal women with symptomatic fibroids eligible for surgical treatment (hysterectomy, myomectomy or UAE). Fibroid symptoms may comprise (but are not limited to) heavy menstrual bleeding, bulk symptoms or pain. Patients are randomised 2:1 in a parallel group design between two treatment arms: 119 patients in the UPA group and 60 patients in the surgery group. Follow up comprises of online questionnaires, outpatient visits and phone appointments on several follow up moments, up to 24 months after surgery or start UPA. Registration details: MYOMEX-2 trial; protocol version 4, date 22−02-2019; NTR6860; NL62638.029.18. All items from the World Health Organization Trial Registration Data Set are provided in the online supplementary file (Appendix-B).